Perceptions of Community Pharmacists Towards Patient Counseling and Continuing Pharmacy Education Programs in Sudan - Hamadouk RM; Yousef BA; Albashair ED; Mohammed FM; Arbab AH (Dove Medical Press, 2023)
Riham M Hamadouk,1 Bashir A Yousef,2 Esra D Albashair,1 Fatimah M Mohammed,1 Ahmed H Arbab3 1Department of Clinical Pharmacy, Faculty of Pharmacy, University of Khartoum, Khartoum, Sudan; 2Department of Pharmacology, Faculty of Pharmacy, University of Khartoum, Khartoum, Sudan; 3Department of Pharmacognosy, Faculty of Pharmacy, University of Khartoum, Khartoum, SudanCorrespondence: Ahmed H Arbab, Department of Pharmacognosy, Faculty of Pharmacy, University of Khartoum, Al-Qasr Ave, Khartoum, 11111, Sudan, Tel +249 991893200, Fax +249 183780696, Email arbabssn@gmail.comBackground: Community pharmacists are uniquely positioned at the heart of communities, and their patient counseling role is the cornerstone for achieving the required therapeutic goals. Therefore, the main objective of this study is to explore the perceptions of community pharmacists regarding patient counseling, and their perception towards continuing pharmacy education programs.Methods: A descriptive, cross-sectional design was performed among randomly selected 238 community pharmacies in Khartoum locality (Sudan) from September 2022 to December 2022. The data were collected using a self-administered questionnaire adopted from a previous study with few minor modifications, which was adding three sociodemographic questions. Descriptive statistics were carried out according to the study objective to analyze the pharmacists' responses.Results: The majority of the community pharmacists gave counseling and understood its importance to the patients, most of them (70.6%) took 1- 5 minutes during the dispensing process. The dose was the most provided information by community pharmacists (26.7%) followed by administration (23.7%) and duration (22.4%). Few (28.2%) of the patients ask the pharmacists about the cost of the medication. Lack of patients' interest (55%) was the major barrier to effective counseling followed by lack of time (47.9%). Almost all (96.2%) pharmacists in this study were interested in continuing pharmacy education programs, and they preferred programs focusing on common diseases (36.6%), and common drugs (30.3%).Conclusion: This study showed that the majority of community pharmacists in the Khartoum locality had positive perceptions toward patient counseling and they were interested in continuing pharmacy education programs.Keywords: community pharmacist, continuing pharmacy education, patient counseling, Sudan